Synthesis, characterization and biological evaluation of thioureas, acylthioureas and 4-thiazolidinones as anticancer and antiviral agents - ÖZSAVCI, DERYA; KÜÇÜKGÜZEL, İLKAY; KULABAŞ, NECLA; BİNGÖL ÖZAKPINAR, ÖZLEM (MARMARA UNIV, FAC PHARMACY, 2017)
In this study, thiourea derivatives [1-4] were synthesized by using 2-amino-4-substituted pyridine compounds and these compounds have been used as the starting materials for synthesis of 2-imino-1,3-thiazolidin-4-one ring [5, 6]. Two different procedures for 4-thiazolidinone ring closure and synthesis method were optimized. The synthesized compounds were identified by the help of elemental analysis, IR, H-1-NMR, C-13-NMR and mass spectral data while the purities of them were proved with TLC. Synthesized compounds were evaluated for their antiviral and anticancer activity. Antiviral activity against Murine norovirus, Yellow fever, Enterovirus and Chikungunya strains of the test compounds were investigated and EC 50 values of these compounds were determined higher than 0,3 mu M. Cytotoxicity of test compounds was examined on NIH3T3 cell line. When the anticancer activity of test compounds was examined against PC-3, A549, HeLa, HT-29, MCF-7, SJSA1 and K562 cell lines, the percent proliferation values of these compounds were observed over 61% for all cell lines.
Keywords: Acylthioureas; anticancer; antiviral; tautomerism; thiourea; 2-amino-1,3-thiazol-4-one; 2-imino-1,3-thiazolidin-4-one; DRUG DISCOVERY; N,N-DISUBSTITUTED THIOUREAS; THIAZOLIDINONE DERIVATIVES; NONNUCLEOSIDE INHIBITORS; ANTITUBERCULOSIS AGENTS; ANTIMICROBIAL ACTIVITY; CYTOTOXIC ACTIVITIES; ACYL THIOUREAS; ANALOGS; MOIETY